An alternative neutron diffractometer performance for strain/stress measurements. Issue 3 (September 2020) - Mikula, Pavol; Saroun, Jan; Ryukhtin, Vasyl; Stammers, James
Abstract : An alternative neutron diffractometer performance, which documents the feasibility of using a high-resolution three-axis neutron diffractometer for elastic and plastic deformation studies of bulk metallic polycrystalline samples, is presented. Contrary to the conventional double-axis setting, the suggested alternative consists of an unconventional three-axis set-up employing a bent perfect crystal monochromator and an analyzer with a polycrystalline sample in between. Though the alternative is, for measurements, much more time-consuming, its sensitivity to the change of the diffraction angle of the sample is, however, substantially higher and permits also plastic deformation studies on the basis of analysis of the diffraction line profiles. Moreover, much larger widths (up to 10 mm) of the irradiated gauge volumes can be investigated when just slightly affecting the angular resolution properties of the experimental setting.